Kaptive 2.0: updated capsule and lipopolysaccharide locus typing for the Klebsiella pneumoniae species complex - Lam, Margaret M. C.; Wick, Ryan R.; Judd, Louise M.; Holt, Kathryn E.; Wyres, Kelly L. (Microbial genomics, 2022)
The outer polysaccharide capsule and lipopolysaccharide (LPS) antigens are key targets for novel control strategies targeting Klebsiella pneumoniae and related taxa from the K. pneumoniae species complex (KpSC), including vaccines, phage and monoclonal antibody therapies. Given the importance and growing interest in these highly diverse surface antigens, we had previously developed Kaptive, a tool for rapidly identifying and typing capsule (K) and outer LPS (O) loci from whole genome sequence data. Here, we report two significant updates, now freely available in Kaptive 2.0 ( https://github.com/katholt/kaptive ): (i) the addition of 16 novel K locus sequences to the K locus reference database following an extensive search of >17 000 KpSC genomes; and (ii) enhanced O locus typing to enable prediction of the clinically relevant O2 antigen (sub)types, for which the genetic determinants have been recently described. We applied Kaptive 2.0 to a curated dataset of >12 000 public KpSC genomes to explore for the first time, to the best of our knowledge, the distribution of predicted O (sub)types across species, sampling niches and clones, which highlighted key differences in the distributions that warrant further investigation. As the uptake of genomic surveillance approaches continues to expand globally, the application of Kaptive 2.0 will generate novel insights essential for the design of effective KpSC control strategies.